Canine ovarian gonadoblastoma with dysgerminoma overgrowth: a case study and literature review - Ana R. Flores; João Lobo; Francisco Nunes; Alexandra Rêma; Paula Lopes; Luís Carvalho; Carla Bartosch; Irina Amorim; Fátima Gärtner (BMC, 2019)
Abstract Background Gonadoblastoma (GB) is a rare mixed germ cell-sex cord-stromal tumour, first described in humans, commonly found in dysgenetic gonads of intersex patients that have a Y chromosome. However, this entity in not recognized in the WHO classification of tumours of genital system of domestic animals. Herein, we describe a case of ovarian gonadoblastoma with proliferation of dysgerminoma and sex cord-stromal tumour components, in a phenotypically and cytogenetically normal bitch. Case presentation A 17-year-old cross-breed bitch had a firm, grey-white multinodular mass in the left ovary. The tumour was submitted to histopathological examination and Y chromosome detected through karyotype analysis and PCR studies. Microscopically, the ovary was almost replaced by an irregular neoplasm composed of three distinct, intermixed elements: dysgerminoma, mixed germ cell-sex cord-stromal tumour resembling human GB and a proliferative sex cord-stromal tumour component. The germ cells of gonadoblastoma and dysgerminoma components were immunoreactive for c-KIT. Sex cord-stromal cells of gonadoblastoma were immunoreactive for α-inhibin. The sex cord-stromal tumour was immunoreactive for AE1/AE3, occasionally for α-inhibin and negative for epithelial membrane antigen (EMA). The karyotype was 78, XX and PCR analysis confirmed the absence of the Y chromosome. Conclusion Based on these findings, a diagnosis of gonadoblastoma with proliferation of dysgerminoma and sex cord-stromal tumour was made. This is the first case of ovarian gonadoblastoma in a female dog.